Inequality and risk - Marcel Fafchamps (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
In poor societies, asset accumulation serves as insurance. It also opens the door to wider inequality. Many societies prohibit certain types of accumulation, such as land sales or indenture contracts. This paper investigates the theoretical relationship between risk sharing, asset accumulation, and long-term inequality. Scenarios with and without growth are contrasted. The paper also examines how asymmetric risk sharing (patronage) interacts with wealth accumulation to generate unequal distribution of assets and consumption while providing insurance to the poor. The paper provides insights for policy related to poverty and insurance. It refers to empirical evidence without providing new empirical findings. – inequality ; poverty ; precautionary savings ; patronage ; mutual insurance ; risk sharing ; wealth distribution
Keywords: O16; D30; 330; Armut; Vermögensverteilung; Kapitalanlage; Risiko; Soziale Mobilität; Theorie; Privatversicherung